Optimization of bioethanol production by using hydroxyapatite as saccharomyces cerevisiae immobilizer - Adilah Anuar (School of Bioprocess Engineering, 2016)
There are two main objectives and several sub-objectives must be carried out in this study. The two main objectives and sub-objectives as listed below; Main Objective, to explore possibility of using customised solid support (hydroxyapatite) to immobilise yeast cell. Sub-Objectives; to optimize and control the particle size by optimizing the synthesis conditions of primary processing steps like stirring rate, sintering temperature and aging time; to characterize the chemical characteristics such as functional group, particle size and morphology, phase determination and chemical stability of hydroxyapatite; to examine the capability of binding ability of yeast to a hydroxyapatite surface by affinity binding. Main Objective; to verify the ability of immobilised yeast cells to be used for bioethanol production. Sub-Objectives; to study the yeast specific surface characteristics; to determine the immobilization efficiency by qualification and quantification analysis; to observe the cell immobilization viability and stability prior to fermentation.